2014
DOI: 10.1186/1471-2393-14-355
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ views on the acceptability of financial incentives for breastfeeding: a qualitative study

Abstract: BackgroundDespite a gradual increase in breastfeeding rates, overall in the UK there are wide variations, with a trend towards breastfeeding rates at 6–8 weeks remaining below 40% in less affluent areas. While financial incentives have been used with varying success to encourage positive health related behaviour change, there is little research on their use in encouraging breastfeeding. In this paper, we report on healthcare providers’ views around whether using financial incentives in areas with low breastfee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Our finding that policymakers prefer shopping vouchers to cash rewards reflects previous qualitative work with both members of the public and health care providers [ 22 , 27 , 41 ]. As previously, we found that participants were particularly concerned about the potential for recipients to use cash rewards to purchase unhealthy commodities such as tobacco and alcohol [ 27 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 80%
“…Our finding that policymakers prefer shopping vouchers to cash rewards reflects previous qualitative work with both members of the public and health care providers [ 22 , 27 , 41 ]. As previously, we found that participants were particularly concerned about the potential for recipients to use cash rewards to purchase unhealthy commodities such as tobacco and alcohol [ 27 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 80%
“…Recently, shopping vouchers were offered to disadvantaged women who breastfeed in the United Kingdom [ 129 ], and limited access to maternity leave was a rationale for payment by a breast milk cooperative in the United States [ 95 ]. These strategies, and the debates surrounding them, are unique to the cultural, legal, political and economic settings in which they arise [ 37 , 38 , 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Financial incentives provided to women contingent on breast feeding evoke concerns about the positive and negative consequences on relationships. 31 Our ecological approach to understanding incentives as events within complex systems suggests that causal pathways are not linear and straightforward. Meanings of incentives and the context in which they are delivered is likely to impact on feasibility, effectiveness and future implementation in the real world.…”
Section: Discussionmentioning
confidence: 99%